Synchrotron X-ray Microtomography with Improved Image Quality by Ring Artifacts Correction for Structural Analysis of Insects. (9th August 2017) - Yao, Shengkun; Zong, Yunbing; Fan, Jiadong; Sun, Zhibin; Zhang, Jianhua; Jiang, Huaidong
Abstract: Ring artifacts are undesirable and complicate the analysis and interpretation of microstructures in synchrotron X-ray microtomography. Here, we propose a new method to improve the image quality of an object by removing the ring artifacts and investigate the efficiency of this process with tomographic images of a dried Tenebrio molitor . In this method, before the tomographic reconstruction, ring artifacts were identified and located in the sinograms as line artifacts. Then, the identified line artifacts were corrected as single point noise via image processing of the original projections. Eventually, the corresponding line artifacts were removed, resulting in reduced ring artifacts in the reconstructed tomographic images. Simulations verified the efficiency of the proposed method. This method was successfully applied for the structural analysis of the insect T. molitor, showing superior performance in reducing ring artifacts in the tomographic image without noticeable loss of structural information.